Pengaruh Kualitas Produk dan Switching Barrier Terhadap Loyalitas Pelanggan - Muhammad Fajar; Nurhayati Nurhayati; Alhapen Ruslin Chandra (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The research was conducted to find out and analyze how product quality and switching barriers influence Telkomsel customer loyalty, both partially and simultaneously. This research used a quantitative approach to 100 respondents, and sampling was carried out using a purposive sampling technique. The results of the determination test show that the customer loyalty variable explained by product quality and switching barrier factors is 77.4%, the remaining 22.6% is influenced or explained by other variables. The results of the T test on the product quality variable show that the calculated t value > t table value is 6.289 > 1.984 and the switching barrier variable shows that the calculated t value > t table is 2.229 > 1.984, meaning that each variable X has a positive and significant influence on variable Y, namely customer loyalty. Telkomsel. The results of the F test show that the calculated f value > f table is 170.690 > 3.09, meaning that product quality and switching barrier together influence Telkomsel customer loyalty among Padang State Polytechnic students.